La seconde surprise de l'amour - Marivaux, Pierre Carlet de Chamblain de 1688-1763 (SOPAT, 2008)
Comedy by Marivaux, in a version staged by the Théâtre Nanterre-Amandiers in November 2007
Format: 16:9, Farbe, kompatibel mit Format 4:3. - Bonus: Interviews with Clotilde Hesme, Micha Lescot, Pascal Bongard, Audrey Bonnet, Roger Jendly, Roch Leibovici, and Luc Bondy
Keywords: French drama (Comedy); Marivaux, Pierre Carlet de Chamblain de / 1688-1763 / Film adaptations; Marivaux, Pierre Carlet de Chamblain de / 1688-1763; Feature films; Film adaptations; Theaterstück; DVD-Video